A review on the analysis of aeromagnetic anomaly and its geological and tectonic applications - Liguo Jiao; Yu Lei; Jiyao Tu; Junhao Zhao (地球与行星物理论评, 2022)
Aeromagnetic anomaly has the obvious advantages of wide coverage, low cost and high lateral resolution in geological structure research, and has been widely used in concealed magmatic rock and faults detection, tectonic characteristics (e.g. subduction zone, continental rift, dike swarm and mantle plume) analysis, magnetic interfaces (including crystalline basement and Curie Point Depth) inversion, regional tectonic division and study on seismogenic tectonic background. Recently, with the rapid development of aeromagnetic survey technology, more and more high-precision and high-resolution aeromagnetic data have been accumulated, and new global/regional aeromagnetic anomaly maps/models have been generated on this basis. In analyzing and inverting the position, shape, trend and buried depth of field source from aeromagnetic anomaly, various boundary identification techniques such as reduction to the pole, upward continuation, derivations (including vertical and horizontal derivative, oblique derivative, analytic signal amplitude and combinations of derivatives), Euler deconvolution and magnetic boundaries or magnetic susceptibility inversion have been developed. This paper organizes and summarizes rock magnetism and uncertainty of interpretation of magnetic anomalies, introduces various magnetic data analysis and inversion methods, reviews the geological and tectonic applications in different aspects, and discusses and prospects the development of aeromagnetic detection, data analysis and tectonic application in the future. As the basis of aeromagnetic anomaly interpretation, the characteristics of susceptibility of rocks are summarized as follows: the susceptibility of minerals is positively correlated with their iron content. Rock susceptibility is mainly determined by the less abundant content of ferromagnetic minerals (mainly magnetite). The current susceptibility measurements are still not representative enough, thus more in-situ detections especially deep rock samplings are in need and three-dimensional susceptibility models of the continental lithosphere need to be established in the future. In the interpretation of aeromagnetic anomalies, attentions should be paid to the influence of uncertainties, which include non-uniqueness of the inverse problem, annulator, demagnetization, field-source superposition and induced-remanent magnetization separation. For various boundary recognition and inversion techniques to detect the location and buried depth of magnetic sources by aeromagnetic anomalies, it is necessary to be familiar with the advantages and limitations of each technique, and select them according to different research objectives. For example, vertical derivative can be used to identify the center of the source, horizontal derivative can be used to identify the boundary, and oblique derivative can be effectively used to identify the deep source. When magnetic anomaly analysis is applied in geological structure study, appropriate means should be selected according to specific structural problems. For example, to detect concealed magmatic rocks or concealed faults near the surface, the first-order vertical derivative or total horizontal derivative analysis can be used. For the buried depth of rock or the deep distribution of fault zone, qualitative analysis of upward continuation, semi-quantitative analysis of Euler deconvolution and quantitative analysis of three-dimensional magnetic susceptibility inversion can be applied.